2001
DOI: 10.1021/jf001221r
|View full text |Cite
|
Sign up to set email alerts
|

Guar Gum Reduces Trichloroethylene Accumulation in the Body by Reducing TCE Absorption and Fat Tissue Mass

Abstract: Two studies were conducted regarding the effects of guar gum on accumulation and metabolism of trichloroethylene (TCE). In study 1, 6- and 14-weeks-old rats were given a single oral dose of 100 mg of trichloroethylene (TCE). Ten hours after administration of TCE, a marked positive correlation was noted between relative fat tissue weights and TCE distribution in fat tissues. Therefore, a small mass of fat tissue apparently limited TCE accumulation. In study 2, each of four groups of rats was fed one of four die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…In studies 1 and 2, we observed that the total amount of HCB accumulated in the fat tissues and liver of the pregnant rats fed the high-fat diet was higher than that of the rats fed the control diet (Tables 3 and 5). In a previous paper, we have already noted a marked positive correlation between the relative fat tissue weight and the distribution of trichloroethylene in perirenal and epididymal fat tissue (24). In this study, because of the increase of these fat tissue weights of the pregnant rats fed the high-fat diet (Table 5), it was considered that large amounts of HCB had accumulated in these fat tissues of the pregnant rats.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In studies 1 and 2, we observed that the total amount of HCB accumulated in the fat tissues and liver of the pregnant rats fed the high-fat diet was higher than that of the rats fed the control diet (Tables 3 and 5). In a previous paper, we have already noted a marked positive correlation between the relative fat tissue weight and the distribution of trichloroethylene in perirenal and epididymal fat tissue (24). In this study, because of the increase of these fat tissue weights of the pregnant rats fed the high-fat diet (Table 5), it was considered that large amounts of HCB had accumulated in these fat tissues of the pregnant rats.…”
Section: Discussionsupporting
confidence: 52%
“…In previous papers, we observed that dietary fiber, especially viscous indigestible polysaccharides, decreased the accumulation of lipophilic organochlorine chemicals in the body by reducing the absorption of these compounds and the fat tissue mass ( , ). We fed pregnant rats a high-fat diet to which was added a large amount of cellulose to maintain a constant metabolizable energy concentration in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Guar gum with viscous hydrocolloids may reduce the rate of gastric emptying and the diffusion of nutrients to the mucosa of the small intestine and increase cecal output [ 18 ]. For example, guar gum changed bile acid pools and intestinal reabsorption to lower cholesterols [ 19 ] and decreased trichloroethylene accumulation in the body by reducing trichloroethylene absorption and fat tissue mass [ 20 ]. In our study, PHGG supplement seems to have a tendency to depress HF increased caloric intake.…”
Section: Discussionmentioning
confidence: 99%
“…1). Numerous studies suggest that dietary guar gum inhibits absorption of lipid-soluble compounds such as cholesterol [1][2][3], lutein [4], canthaxanthin [4], a-tocopherol [4], 1,1,2-trichloroethylene [5], and 2,3,7,8tetrachlorodibenzo-p-dioxin [6]. One of the characteristics of guar gum is that it is a non-specific absorption inhibitor of any type of lipid-soluble compound.…”
Section: Introductionmentioning
confidence: 99%